PENGARUH TEKNIK PEMBELAJARAN TREFFINGER TERHADAP KEMAMPUAN BERPIKIR KREATI(KUASI EKSPERIMEN PADA SISWA KELAS X SMA DI BANDUNG) - Butar-Butar, Agustina (Universitas Nusa Cendana, 2023)
This research is based on problems according to conditions in schools. The fact is that students look passive when teaching and learning activities take place, and students' creativity is not visible. Efforts are made to encourage students' creative minds by using the Treffinger Technique in learning. This research was conducted to determine the effect of Treffinger learning on students' creative thinking in class X at SMA Kristen 3 Bina Bakti and SMA N1 Parongpong Bandung. In this study, the method used was quasi-experimental, consisting of 56 students for the experimental and 54 for the control classes. The research data was collected through a written exam (pretest and posttest) with 6 essay questions. After analyzing the data using the univariate test, the results show that: 1. It was found that there was a difference between students' creative thinking using finger learning techniques which was higher than students using conventional learning; 2. It was found that there was a difference in the creative thinking of students who used the Trefinger learning technique between Bina Bakti 3 Christian High School and Parongpong 1 Public High School; 3. The type of school and the learning skills used to increase proficiency in creative thinking are separate.